EVALUATION OF THE TEACHING OF ENGLISH LANGUAGE IN SENIOR SECONDARY SCHOOLS IN GOMBE STATE (Journal of Guidance and Counselling Studies, 2021)
This study adopted the evaluative survey research design. The area of the study covered Gombe South Educational Zone comprising Balanga, Billiri, Kaltungo and Shongom Local Government Areas of Gombe State. Five research questions were formulated to guide the study. The study population comprised 113 English language teachers in all the study area in the State. Random sampling technique was used to draw one education zone (Gombe South Education Zone) out of the three education zones in Gombe State. Data were collected using a researcher-made questionnaire titled Teachers of English Language Questionnaire (TELEQ). The instrument was validated by three experts from the Department of Arts Education, Science Education and the Institute of Education of the University of Nigeria, Nsukka. The reliability coefficient of obtained were 0.84, 0.84, 0.85, and 0.75 for section B, C, D, and E respectively, with an overall coefficient of 0.80. Data collected was analyzed using percentages, mean and standard deviation. The finding of the study revealed that there were many methods used by English teachers in Gombe state secondary schools to teach English language, but there were some methods of teaching English language they do not utilize. Some instructional materials used for the teaching of English language in secondary schools in the state are available, while many of them are not available. Many classroom physical facilities for teaching English language in secondary schools in the state are moderately adequate while few of them are less adequate. Based on the results, it was recommended that there should be adequate engagement of English teachers in various secondary schools in Gombe State, and teaching facilities should be properly upgraded in various secondary schools in Gombe State.